2021
DOI: 10.1017/jfm.2021.233
|View full text |Cite
|
Sign up to set email alerts
|

Dilute dispersion of compound particles: deformation dynamics and rheology

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…Recently, we analyzed the time-dependent deformation dynamics and non-Newtonian rheology of a dilute dispersion of compound particles in a generalized linear flow using analytical methods. 26,27 Zhang et al 28 reported the non-monotonic variation of viscosity and yield stress in the dense suspension of compound particles. Apart from interesting rheological properties, 27 these structures are associated with rich dynamics and hydrodynamic flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we analyzed the time-dependent deformation dynamics and non-Newtonian rheology of a dilute dispersion of compound particles in a generalized linear flow using analytical methods. 26,27 Zhang et al 28 reported the non-monotonic variation of viscosity and yield stress in the dense suspension of compound particles. Apart from interesting rheological properties, 27 these structures are associated with rich dynamics and hydrodynamic flows.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Zhang et al 28 reported the non-monotonic variation of viscosity and yield stress in the dense suspension of compound particles. Apart from interesting rheological properties, 27 these structures are associated with rich dynamics and hydrodynamic flows. 26,29 For instance, in our previous study, we have shown that the hydrodynamic resistance offered by the concentric compound particles can be varied significantly by varying the size of the confining droplet relative to the encapsulated particle and the viscosity of the droplet fluid and the continuous fluid.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, droplets/bubbles deform in linear shear flows, and end up resting in steady flows or breaking up when viscous force exerted by the surrounding fluid dominates surface tension (Stone 1994). The dynamics of droplets in shear is characterised by droplet deformation, resulting from the competition among viscous shear, inertia and surface tension (Singh & Sarkar 2011; Singeetham, Chaithanya & Thampi 2021; Yi et al. 2022).…”
Section: Introductionmentioning
confidence: 99%